Il trascendentale pulchrum in Tommaso d’Aquino, secondo Hans Urs von Balthasar - Villagrasa LC, Jesús (Alpha Omega, 2012)
This paper presents Aquinas’s position on beauty as a transcendental, the metaphysics behind it, and von Balthasar’s interpretation of it. To do so it considers the meaning of von Balthasar’s theological aesthetics, as presented in the first volume of The Glory of the Lord, and the implications of making beauty the point of departure for theology. On these grounds it is possible to better appreciate how von Balthasar reads Aquinas’s account of beauty as a transcendental (The Glory of the Lord, vol. 4). The theological importance of this conception of beauty is brought out in Epilogue.